2007
DOI: 10.1200/jco.2006.07.1514
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind, Placebo-Controlled Trial of Erythropoietin in Non–Small-Cell Lung Cancer With Disease-Related Anemia

Abstract: An unplanned safety analysis suggested decreased overall survival in patients with advanced NSCLC treated with epoetin alfa. Although infrequent, other similar reports highlight the need for ongoing trials evaluating erythropoietin receptor agonists to ensure that overall survival is monitored closely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
233
3
7

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(247 citation statements)
references
References 26 publications
4
233
3
7
Order By: Relevance
“…Several placebo-controlled randomized controlled phase III trials were initiated to test this strategy, or to test EPO in combination with chemotherapy, and the outcome was a surprise. Despite a demonstrable improvement in hemoglobin concentration after EPO [5], the trials consistently found a worse tumor outcome in the EPO arm [6][7][8][9][10]. The biological mechanism behind this unexpected finding remains controversial [11] although it is likely the result of EPO acting as a survival/growth factor for cancer cells expressing erythropoietin surface receptors…”
Section: Evidence-based Medicine and Randomized Controlled Trialsmentioning
confidence: 99%
“…Several placebo-controlled randomized controlled phase III trials were initiated to test this strategy, or to test EPO in combination with chemotherapy, and the outcome was a surprise. Despite a demonstrable improvement in hemoglobin concentration after EPO [5], the trials consistently found a worse tumor outcome in the EPO arm [6][7][8][9][10]. The biological mechanism behind this unexpected finding remains controversial [11] although it is likely the result of EPO acting as a survival/growth factor for cancer cells expressing erythropoietin surface receptors…”
Section: Evidence-based Medicine and Randomized Controlled Trialsmentioning
confidence: 99%
“…[5] However, similar to the aforementioned articles, there were no findings of mesenteric thrombosis as a thrombotic complication of erythropoiesis-stimulating drugs. [313]…”
Section: Discussionmentioning
confidence: 99%
“…This report is the first case of mesenteric infarction due to iatrogenic polycythemia in the literature. [313]…”
Section: Introductionmentioning
confidence: 99%
“…However, the conflicting effects of ESAs were recently described in distinct studies [70][71][72]. Indeed, besides cardiovascular and thromboembolic events in erythropoietin-treated patients, several phase II and III trials showed a significant deterioration of cancer patients survival [73][74][75].…”
Section: Deregulation Of Erythropoiesis By Tnfα α α α In Inflammationmentioning
confidence: 99%